2011
DOI: 10.1186/1477-7827-9-136
|View full text |Cite
|
Sign up to set email alerts
|

Embryotoxicity assays for leached components from dental restorative materials

Abstract: BackgroundCurrently, there are no suitable assays available to evaluate the embryotoxicity of leached components from restorative dental materials.MethodsThe effect of the medium conditioned by composites and amalgam on mouse blastocysts in vitro was tested. The materials were also subcutaneously implanted, and the effect of the medium supplemented with serum from the host blood was evaluated in the embryotoxicity assay. The embryo implantation rate in the material-transplanted mothers was also evaluated.Resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 20 publications
0
18
0
Order By: Relevance
“…Many patients go to the dentist to improve and correct their smile, in order to achieve a more pleasant and natural appearance. The dentist can meet and satisfy the patient's esthetic needs by modifying the morphological and chromatic characteristics (shape and color) of the teeth, adopting increasingly effective techniques of adhesive and restorative dentistry …”
Section: Introductionmentioning
confidence: 99%
“…Many patients go to the dentist to improve and correct their smile, in order to achieve a more pleasant and natural appearance. The dentist can meet and satisfy the patient's esthetic needs by modifying the morphological and chromatic characteristics (shape and color) of the teeth, adopting increasingly effective techniques of adhesive and restorative dentistry …”
Section: Introductionmentioning
confidence: 99%
“…In relation to potential hazards, a study by Libonati et al. [ 95 ] demonstrated that leaked components from nanocomposite materials caused embryotoxicity in mouse blastocyst in vitro , but the reverse was the case with no toxicity when subcutaneously implanted in vivo . Similarly, a lower toxicity was recorded for orthodontic adhesive nanocomposite composed of titanium dioxide (TiO 2 ) NPs (at 1% by weight of TiO 2 NPs) compared to the NP free material [ 96 , 97 ].…”
Section: Nanodentistry and Maxillofacial Pathologymentioning
confidence: 99%
“…It was concluded that incorporation of 1% by weight of Ti0 2 nanoparticles to the composite structure does not result in additional health hazards compared to that occurring with pure adhesive. [ 59 ] In another study,[ 60 ] it was reported that leached components from composite material induced embryotoxicity in mouse blastocyst in vitro , while no toxicity was observed when subcutaneously implanted in vivo .…”
Section: Hazards Of Nanoparticlesmentioning
confidence: 99%